The effect of CBT national examination policy in terms of senior high school students’ cognitive readiness and anxiety facing mathematics tests in DIY Province - Eny Sulistyaningsih; Sugiman Sugiman (Program Studi Pendidikan Matematika Program Pascasarjan Universitas Negeri Yogyakarta, 2016)
The purpose of this study was to determine the influence of CBT and PBT national examination in terms of students’ cognitive readiness and anxiety facing mathematics national examination in DIY province, the influence of major in terms of students’ cognitive readiness and anxiety facing mathematics national examination in DIY Province, and the interaction between national examination and major. This research was descriptive explorative and the method was ex-post facto. The population was all of natural and social science high school students in grade XII in DIY province. The number of sample used was 654 students The results showed that there was influence of national examination in terms of students’ cognitive readiness and anxiety facing national examination. CBT and PBT national examination did not influence the cognitive readiness facing national examination, CBT and PBT national examination influence in national examinations in terms of students’ anxiety facing national examination. The average score of the students’ anxiety facing CBT national exam was greater than that of the students’ anxiety facing PBT national examination. There was no effect caused by differences in majoring in terms of cognitive readiness and national examination math anxiety; and there was no interaction between the different types of national examinations and majors.